Management of risks - a Paradox? - Nilsen, Aud Solveig; Leonhardsen, Mette (2016)
Session description from the NEON Conference (Nettverk for organisasjonsforskning i Norge). The conference was held 23.11.16 - 24.11.16, in Tromsø.